Phytochemical and Pharmacological Studies and Evidence-Based Indications of Babuna (Matricaria Chamomilla L.): A Review (AYUSHDHARA, 2022)
Babuna (Matricaria chamomilla L.syn. Matricaria recutita or Chamomilla recutita L.) is a well known medicinal plant used in Unani System of Medicine since centuries. It belongs to the family Asteraceae. Detailed description of this herb is found in classical literature of Unani Medicine. Babuna has been used for various therapeutic, cosmetic and nutritional purposes since centuries which have been proved through its traditional use and scientific research. Variety of pharmacological actions of Babuna such as Muhallil (resolvent), Musakkin-e-Alam (Analgesic), Mudir al Bawl (Diuretic), Mudir Hayd (Emmenogogue), Muarriq (Diaphoretic), Muqawwi Mida (Stomachic), Kasir-i-Riyah (Carminative), Muqawwi-i- Dimaag (Brain Tonic), Muqawwi-i-Asab (nervine tonic) etc., have been mentioned in classical books of Unani System of Medicine. Various phytochemical studies have shown presence of different types of bioactive constituents in this herb which on further experiments and clinical studies have shown multiple pharmacological properties which are in consonance with the actions documented in Unani literature. The present article has provided a review of pharmacological actions and therapeutic uses of Babuna in Unani Medicine, in the light of knowledge present in Unani literature as well as recent scientific studies and experimental data available on Matricaria chamomilla.